Tourist Attraction, Motivation, and Prices Influence on Visitors' Decision to Visit the Cikandung Water Sources Tourism Object - Irena Novarlia (Budapest International Research and Critics University, 2022)
This research is motivated by the increasing income and welfare of consumers' needs for tourism services can not be separated from the decision to visit tourists based on tourist attraction, motivation, and the price of a tourist attraction. The purpose of this study was to determine the effect of tourist attraction, motivation, and price on the decision to visit the Cikandung Springs tourist attraction. The data analysis method used is multiple linear regression analysis and the proof of the hypothesis is done by t test, F test and coefficient of determination test (R2). Samples were taken from 150 respondents. The results of multiple linear regression analysis obtained the equation Y=3,487+0,411X1+0,415X2+0,420X3. The results of the t-test indicate that the variables of tourist attraction, motivation, and price have a significant effect on the decision to visit the Cikandung Springs tourist attraction. The results of the F test indicate that the variables of tourist attraction, motivation, and price have a significant effect on the decision to visit the Cikandung Springs tourist attraction. The results of the coefficient of determination (R2) explain that tourist attraction, motivation, and price affect the decision to visit the Cikandung Springs tourist attraction by 36.7%. Based on the results of the study, it is recommended that tourist attraction managers always pay attention to the factors of tourist attraction, motivation, and price in developing tourist objects because the results of the study prove a significant influence on the decision to visit tourists.